Improvement of Public Control over the Use of Land Resources as an Important Aspect of Modernisation of the Ukrainian State in the XXI Century - Kostruba, Anatoliy V.; Kulynych, Pavlo F. (International Journal of Criminology and Sociology, 2021)
For the rational use and protection of land, the issue of effective implementation of land reform remains relevant. An important aspect in increasing the importance of this reform is the state's interest in land use. It is the main subject of land use control and protection. However, the consolidation of provisions on land protection in the Constitution of Ukraine demonstrates that the preservation of land resources in all spheres of public relations constitutes an important component of the legal policy of Ukraine in the land sphere and the constitutional obligation to protect land not only to the state but also to citizens, legal entities, and local communities. The purpose of the study is to analyse the legislative practice of compliance with the rules of rational use and protection of land resources. The main research methods were general science - analysis and synthesis, induction and deduction. The study considers the role of the state, people, local governments in the management and control of land resources. The main statutory documents governing the use of land resources were considered. Amendments to the legislation of Ukraine in the field of land ownership were proposed to delegate the powers of control of land resources between the state and local communities. The possible expansion of the land powers of the self-government bodies of the united territorial communities was considered. The practical significance of the study lies in the possibility of using results in the development of projects to improve public control over the use of land resources.